1958
DOI: 10.2134/agronj1958.00021962005000050006x
|View full text |Cite
|
Sign up to set email alerts
|

Dry Weights and Germination of Developing Oat Seeds1

Abstract: Synopsis Oat seeds reached a near‐maximum dry weight when they contained as high as 45% moisture. Very little dry matter was laid down after they dried to this moisture content. Germination increased with maturity up to 20 to 28 days after anthesis even though a few germinated when harvested 4 days after anthesis. A pregermination chilling treatment of oat seeds at 4° C. for 10 days considerably increased the germination of prematurely harvested seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1961
1961
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The general process of ripening in cereals, especially in wheat, has been described in several papers, e.g. Brenchley (191 2), Saunders (1928), Koblet (1940), Frey et al (1958), Rawson & Evans (1970), Walpole & Morgan (1970). Duffus & Rosie (1976).…”
mentioning
confidence: 99%
“…The general process of ripening in cereals, especially in wheat, has been described in several papers, e.g. Brenchley (191 2), Saunders (1928), Koblet (1940), Frey et al (1958), Rawson & Evans (1970), Walpole & Morgan (1970). Duffus & Rosie (1976).…”
mentioning
confidence: 99%
“…observed that larger oat seeds produced plants with above-average heights at maturity, Frey et al (1958) found that the oat genotypes they studied were of similar size at maturity, even though seed and seedling weights were closely correlated. Discrepancies have also been found for wheat and barley, some researchers reporting a seed size effect on plant height (Pinthus and Osher 1966;Bhatt and Derera 1973) and others the lack of an effect (Kaufmann and Guitard 196'7).…”
mentioning
confidence: 87%
“…A'L THOUGH viability and dry weight accumulation of fl. developing caryopses of wheat ( 8), oats ( 1,2), and barley ( 4) have been studied, little information of this type is available for grain sorghum. Data on viability of immature sorghum seeds should be valuable to plant breeders, and seed producers should find data on time of maximum dry weight accumulation and viability useful.…”
mentioning
confidence: 99%
“…IMaximum dry weight accumulation has been reported to occur when grain moisture percentage approximated 40% in wheat and barley (5, 7,8) and 47% in bromegrass (3). Frey et al (2) have shown that differences in environmental conditions in different years may influence rate of maturation in oats.…”
mentioning
confidence: 99%